Analisis Implementasi Shared Leadership: Studi Kasus pada CV Esterlie Mandiri - Gilang Maulana; M. Fahmi Siddiq Afif; Ridho Ilhami; Sani Rizqi Diyaaul Haq; Hani Humaeriyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the Implementation of Shared Leadership: A Case Study at CV Esterlie Mandiri. This study uses a qualitative approach with a case study method. Data analysis employed thematic analysis techniques, where data collected from interviews, participant observation, and organizational documents were organized, discussed, and interpreted to identify key themes related to the implementation of shared leadership at CV Esterlie Mandiri. The analysis of the implementation of shared leadership at CV Esterlie Mandiri revealed that the company has implemented the three dimensions of shared leadership according to Carson et al.'s (2007) framework—shared purpose, social support, and voice—through various concrete mechanisms. These mechanisms include the formation of cross-functional teams, rotation of leadership in meetings, and participatory discussion forums that facilitate the distribution of leadership influence among team members. This implementation has had a positive impact on organizational performance.